An Overlay Routing Protocol for Video over sparse MANETs in Emergencies - Cabrero, Sergio; Pañeda, Xabiel G.; Plagemann, Thomas; Melendi, David; García, Roberto (Cadernos de Informática, 2011)
Video delivery over a mobile ad-hoc network that can be deployed by members of an emergency service in an incident zone is an appealing tool for emergency and rescue services, but has not be studied yet. In order to design and test a suitable solution, we have generated realistic evaluation scenarios by modeling fireman action plans and GPS traces from real situations. The Emergency Overlay Routing (EOR) protocol is a reactive protocol integrated into a store-carry-forward architecture. It selects ferry nodes to transport video data from a camera in the Incident Area to the Incident Chief’s node, looking for the minimum delay, but reliable, candidate. The evaluation of EOR shows its superiority to the well-known DTN routing protocol, PROPHET, under this conditions.